The valuation channel of external adjustment - Fabio Ghironi; Jaewoo Lee; Alessandro Rebucci (Federal Reserve Bank of Boston, 2009)
International financial integration has greatly increased the scope for changes in a country's net foreign asset position through the valuation channel of external adjustment, namely capital gains and losses on the country's external assets and liabilities. We examine this valuation channel theoretically in a dynamic equilibrium portfolio model with international trade in equity that encompasses complete and incomplete asset market scenarios. By separating asset prices and quantities in the definition of net foreign assets, we can characterize the first-order dynamics of both valuation effects and net foreign equity holdings. Firstorder excess returns are unanticipated and i.i.d. in our model, but capital gains and losses on equity positions feature persistent, anticipated dynamics in response to productivity shocks. The separation of prices and quantities in net foreign assets also enables us to characterize fully the role of capital gains and losses versus the current account in the dynamics of macroeconomic aggregates. Specifically, we disentangle the roles of excess returns, capital gains, and portfolio adjustment for consumption risk sharing when financial markets are incomplete, showing how these different channels contribute to dampening (or amplifying) the impact response of the cross-country consumption differential to shocks and to keeping it constant in subsequent periods.
Keywords: F32; F41; G11; G15; 330; current account; equity; net foreign assets; risk sharing; valuation; Internationaler Finanzmarkt; Integration; Wertpapierhandel; Entscheidung bei Risiko; Zahlungsbilanzungleichgewicht; Transmissionsmechanismus; Dynamisches Modell